THE CURRICULAR COMMON NATIONAL BASE FOR CHILD EDUCATION AND FIELDS OF EXPERIENCE: CONCEPTUAL REFLECTIONS BETWEEN BRAZIL AND ITALY - Fernandes Ariosi, Cinthia Magda [UNESP] (Fundacao Univ Tocantins, 2019)
The expression fields of experience appears in the Common National Curriculum Base as a proposal of curricular organization for Early Childhood Education.This article aims to: discuss the text of the BNCC for early childhood education, explaining the concept of fields of experience, their origin, legal basis in Brazil and Italy. The guiding questions were: what origin of the expression fields of experience? What is the the oretical basis of this expression for BNCC-EI? What is the link of this concept with the possibility of dialogue between Brazilians and Italians? Data were collected through bibliographic research and document analysis. The theoretical framework was formulated from the writings of the Italian and Brazilian approach to early childhood education and the legislations of both countries.The BNCC-EI is very similar to the Italian curricular indications, but it would be possible to build a curricular proposal with authorship and own identity of Brazilians.
Keywords: Fields of experience; BNCC-EI; Curriculum; Child education; Reggio Emilia